2017
DOI: 10.1002/tea.21394
|View full text |Cite
|
Sign up to set email alerts
|

Second graders’ emerging particle models of matter in the context of learning through model‐based inquiry

Abstract: In this paper, we present a study of second graders’ learning about the nature of matter in the context of content‐rich, model‐based inquiry instruction. The goal of instruction was to help students learn to use simple particle models to explain states of matter and phase changes. We examined changes in students’ ideas about matter, the coherence of their emerging particle models, and how classroom science discourse influenced students’ learning. The study was conducted in two second grade classrooms in a rura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 58 publications
(98 reference statements)
2
28
0
Order By: Relevance
“…This, in turn, yields an explanatory basis from which students can engage in hypothesis testing as they actively explore and interpret exploratory outcomes. Likewise, activities such as generating and manipulating models of atomic structure remain core to explanatorily coherent inquiry-based interventions focused on the particulate structure of matter, even as it is also noted that, as with any instruction, the models and activities can themselves sometimes promote misconceptions—outcomes that should be anticipated as early as possible (e.g., Haeusler & Donovan, 2017; Samarapungavan et al, 2017; see also Lehrer & Schauble, 2012; Vosniadou, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, yields an explanatory basis from which students can engage in hypothesis testing as they actively explore and interpret exploratory outcomes. Likewise, activities such as generating and manipulating models of atomic structure remain core to explanatorily coherent inquiry-based interventions focused on the particulate structure of matter, even as it is also noted that, as with any instruction, the models and activities can themselves sometimes promote misconceptions—outcomes that should be anticipated as early as possible (e.g., Haeusler & Donovan, 2017; Samarapungavan et al, 2017; see also Lehrer & Schauble, 2012; Vosniadou, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…They also converge with other findings suggesting that, when offered instruction that scaffolds the construction of coherent mechanistic frameworks and models, young children can elaborate and apply accurate theories of various pivotal counterintuitive phenomena (e.g., Lehrer & Schauble, 2012; Nguyen, McCullough, & Noble, 2011). Second graders, for example, can learn and use coherent particulate conceptions of matter that not only run counter to their macroscopic perceptual experiences but also to their teleological and essentialist intuitions about materials (e.g., “matter only exists if it has a function, and phase changes reflect different material kinds”; Samarapungavan, Bryan, & Wills, 2017; for other suggestive evidence, see Haeusler & Donovan, 2017; Stein, Hernandez, & Anggoro, 2010).…”
Section: A Mechanistic Approach To Counterintuitive Science Instructionmentioning
confidence: 99%
“…However, what Richard Feynman envisaged as 'a little imagination and thinking' turns out to be a tremendous challenge in the classroom. Indeed, studies of students' conceptions about the particulate nature of matter have repeatedly shown that middle and high school students have significant difficulties in establishing an adequate understanding of particle models (Adbo & Taber, 2009;Griffiths & Preston, 1992;Harrison & Treagust, 1996;Samarapungavan et al, 2017). Moreover, when it comes to students' conceptions about particle models, vast discrepancies have been documented in their degree of coherence (Gómez et al, 2006;Wiser & Smith, 2008), and research suggests a long-term spiral approach to be best suited for the teaching of the particulate nature of matter (Margel et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a whole, the elementary grade‐band expectations described above include but do not foreground mechanistic reasoning; and when those expectations do state that students should engage in formulating causal relationships, it is in the context of experimental testing (i.e., evidence‐based causal pattern‐seeking) or describing and representing a scientific principle (using “an analogy, example, or abstract representation to describe a scientific principle”) as opposed to delving more deeply into the underlying mechanism 7 . These emphases neither take advantage of students' abilities to reason mechanistically (Bolger, Kobiela, Weinberg, & Lehrer, 2012; Russ et al, 2009; Samarapungavan, Bryan, & Wills, 2017) nor fully embrace the Framework for K‐12 Science Education (NRC, 2012), which suggested that upper elementary students “begin to consider what might be causing these patterns and relationships (p. 88)” from early on and start to ask questions like “What mechanisms caused that to happen? (p. 89).”…”
Section: Discussionmentioning
confidence: 99%